vcfpp: a C++ API for rapid processing of the variant call format - Li, Zilong (Bioinformatics (Oxford, England), 2024)
Motivation Given the widespread use of the variant call format (VCF/BCF) coupled with continuous surge in big data, there remains a perpetual demand for fast and flexible methods to manipulate these comprehensive formats across various programming languages. Results This work presents vcfpp, a C++ API of HTSlib in a single file, providing an intuitive interface to manipulate VCF/BCF files rapidly and safely, in addition to being portable. Moreover, this work introduces the vcfppR package to demonstrate the development of a high-performance R package with vcfpp, allowing for rapid and straightforward variants analyses. Availability and implementation vcfpp is available from https://github.com/Zilong-Li/vcfpp under MIT license. vcfppR is available from https://cran.r-project.org/web/packages/vcfppR.